Activated Mucosal-associated Invariant T Cells Have a Pathogenic Role in a Murine Model of Inflammatory Bowel DiseaseSummary - Yusuke Yasutomi (Elsevier, 2022)
Background & Aims: Mucosal-associated invariant T (MAIT) cells are innate-like T cells restricted by major histocompatibility complex-related molecule 1 (MR1) and express a semi-invariant T cell receptor. Previously, we reported the activation status of circulating MAIT cells in patients with ulcerative colitis (UC) was associated with disease activity and that these cells had infiltrated the inflamed colonic mucosa. These findings suggest MAIT cells are involved in the pathogenesis of inflammatory bowel disease. We investigated the role of MAIT cells in the pathogenesis of colitis by using MR1−/− mice lacking MAIT cells and a synthetic antagonistic MR1 ligand. Methods: Oxazolone colitis was induced in MR1−/− mice (C57BL/6 background), their littermate wild-type controls, and C57BL/6 mice orally administered an antagonistic MR1 ligand, isobutyl 6-formyl pterin (i6-FP). Cytokine production of splenocytes and colonic lamina propria lymphocytes from mice receiving i6-FP was analyzed. Intestinal permeability was assessed in MR1−/− and i6-FP-treated mice and their controls. The effect of i6-FP on cytokine production by MAIT cells from patients with UC was assessed. Results: MR1 deficiency or i6-FP treatment reduced the severity of oxazolone colitis. i6-FP treatment reduced cytokine production in MAIT cells from mice and patients with UC. Although MR1 deficiency increased the intestinal permeability, i6-FP administration did not affect gut integrity in mice. Conclusions: These results indicate MAIT cells have a pathogenic role in colitis and suppression of MAIT cell activation might reduce the severity of colitis without affecting gut integrity. Thus, MAIT cells are potential therapeutic targets for inflammatory bowel disease including UC.